Dense Artery Sign - Anam, Ahmad Mursel; Polash, Mohammd Mufizul Islam; Rabbani, Raihan; Shumy, Farzana (Bangladesh Critical Care Journal, 2013)
DOI: http://dx.doi.org/10.3329/bccj.v1i2.17208 Bangladesh Crit Care J September 2013; 1 (2): 111-112